The entrepreneurial orientation of general practitioners-Current theory and practice in the Czech Republic - Marciánová, Pavla; Pirožek, Petr (Health policy (Amsterdam, Netherlands), 2023)
BACKGROUND: Since 2010, the Czech Republic has been experiencing a spontaneous phenomenon in which General Practitioner (GPs) practices have been transferred to a legal limited liability company as defined by the Commercial Code. OBJECTIVES: Our research attempted to ascertain the reasons that induced GPs to change their legal form, thereby opting for an entrepreneurial orientation (EO). A second objective was to measure the impact of this change on the healthcare performance of GP practices. METHODOLOGY/APPROACH: We used exploratory research to examine this phenomenon in healthcare service provision. Data from 131 questionnaires was evaluated using an exploratory survey with descriptive statistics. To assess the healthcare performance of GP practices, we used secondary data from the Institute of Health Information and Statistics of the Czech Republic. FINDINGS: The GPs interviewed considered their practices to be businesses. Their decision to change to a limited company form was influenced by the possibility of selling or transferring the business, employment sustainability and job security, and advantages related to cost structure and taxation. Our study shows that, in a generational exchange, the change in legal form enhances the sustainability and operation of the practice within the context of the current demands for high-quality healthcare.
Keywords: průzkumy a dotazníky; Surveys and Questionnaires; kvalita zdravotní péče; postoj zdravotnického personálu; Performance; Humans; Česká republika; praktičtí lékaři; lidé; Attitude of Health Personnel; General medical practice; praktické lékařství; General Practitioners; Entrepreneurial orientation; Quality of Health Care; Transfer of legal forms; Czech Republic; General Practice